Transforming Growth Factor Beta (TGFβ1) and Epidermal Growth Factor (EGF) as Biomarkers of Leishmania (V) braziliensis Infection and Early Therapeutic Response in Cutaneous Leishmaniasis: Studies in Hamsters - Montoya, Andrés; Yepes, Lina; Bedoya, Alexander; Henao, Raúl; Delgado, Gabriela; Vélez, Iván D.; Robledo, Sara M. (Frontiers in Cellular and Infection Microbiology, 2018)
Introduction: In cutaneous leishmaniasis, the host immune response is responsible for the development of skin injuries but also for resolution of the disease especially after antileishmanial therapy. The immune factors that participate in the regulation of inflammation, remodeling of the extracellular matrix, cell proliferation and differentiation may constitute biomarkers of diseases or response to treatment. In this work, we analyzed the production of the growth factors EGF, TGFβ1, PDGF, and FGF during the infection by Leishmania parasites, the development of the injuries and the early response to treatment. Methodology: Golden hamsters were infected with L. (V) braziliensis. The growth factors were detected in skin scrapings and biopsies every 2 weeks after infected and then at day 7 of treatment with different drug candidates by RT-qPCR. The parasitic load was also quantified by RT-qPCR in skin biopsies sampled at the end of the study. Results: The infection by L. (V) braziliensis induced the expression of all the growth factors at day 15 of infection. One month after infection, EGF and TGFβ1 were expressed in all hamsters with inverse ratio. While the EGF and FGF levels decreased between day 15 and 30 of infection, the TGFβ1 increased and the PGDF levels did not change. The relative expression of EGF and TGFβ1 increased notably after treatment. However, the increase of EGF was associated with clinical cure while the increase of TGFβ1 was associated with failure to treatment. The amount of parasites in the cutaneous lesion at the end of the study decreased according to the clinical outcome, being lower in the group of cured hamsters and higher in the group of hamsters that had a failure to the treatment. Conclusions: A differential profile of growth factor expression occurred during the infection and response to treatment. Higher induction of TGFβ1 was associated with active disease while the higher levels of EGF are associated with adequate response to treatment. The inversely EGF/TGFβ1 ratio may be an effective biomarker to identify establishment of Leishmania infection and early therapeutic response, respectively. However, further studies are needed to validate the utility of the proposed biomarkers in field conditions.